Pendampingan dan Pelatihan Metodologi Penelitian Kuantitatif Bagi Mahasiswa Pusat Studi MGM - Prasetyo, Agung; Ndari, Arum Vika; Tanzilla, Armeyta Putri; Saputro, Rujianto Eko; Wijaya, Anugerah Bagus; Hamdi, Aulia; Suliswaningsih, Suliswaningsih (Jurnal Pengabdian Mitra Masyarakat (JPMM), 2023)
AMIKOM University in Purwokerto, through its 6 study centers, requires and trains each student to write scientific papers, such as scientific reports, articles, theses, and scientific journals. The survey results agreed upon by the partners highlight several issues in this program. These issues include students' lack of understanding regarding the core issues in research, insufficient preparedness in creating suitable materials, theories, and references before designing a research proposal, and ambiguity in formulating research problems. Students also lack understanding of the research methodology they will use and are not accustomed to writing and citing scientifically. Many students still do not understand research methodology and are less skilled in designing research proposals. The learning process in lectures often feels monotonous because they are dominated by speeches and Q&A sessions, and students are not actively involved enough in searching and digging for information or theories. Only a few students get the opportunity to participate in guided exercises in formulating problems, selecting theories relevant to the problem, and choosing research methodology. This becomes a challenge that must be addressed in this program. The solution to these problems is to conduct training and mentoring for students to improve the quality of student research. In implementing this service, we use the Direct Action Method. This method includes several steps, namely Diagnosing, Action Planning, Action Taking, Evaluating, and Learning. These steps refer to the diagnostic process, action planning, action implementation, evaluation, and learning. This service has been successful in increasing the capacity of student human resources and students' abilities in research, which will benefit students in the future.